"A Lot of Flexibility within the Structure": Academic Library Collection Development & E-Resources Management from an Athletics Perspective. Issue 4 (2nd October 2019) - Lowe, Randall A.
Abstract: There is an established history of academic libraries collaborating with their institutions' athletics departments to provide learning and research support to student-athletes in order to achieve positive educational outcomes. It is rarer to find documented the effect that athletics has had on the professional life of an academic librarian. The author details how the skills acquired and lessoned learned being an athlete and collegiate coach directly influenced his approach to providing leadership in various collection development and electronic resources management initiatives at a medium-sized academic library.